2022
DOI: 10.1093/jac/dkac021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative polymyxin B pharmacokinetics in patients receiving extracorporeal membrane oxygenation

Abstract: Objectives To describe polymyxin B pharmacokinetics in patients receiving veno-venous extracorporeal membrane oxygenation (ECMO) in comparison with critically ill patients without ECMO support and to explore potential covariates that could affect the pharmacokinetics in this group of patients. Patients and methods In 13 critically ill patients on ECMO and in 21 critically ill patients without ECMO support, 6–8 blood samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
6
2
Order By: Relevance
“…In our study, the mean clearance of all patients and those with ECMO support were 0.026 and 0.027 L/h/kg, respectively, very similar to the results of another study (0.0276 L/h/kg), 12 which used a two‐compartment model to describe the PK profile of 24 critically ill patients without ECMO support, suggesting that the impact of ECMO on the polymyxin B PK was likely to be minimal. Compared with another study that included patients with ECMO support, 24 our study showed a higher polymyxin B CL and a lower Vd, and hypoalbuminemia may be the parameter that may explain such PK differences (34.2 ± 3.1 vs. 29.8 ± 1.6).…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…In our study, the mean clearance of all patients and those with ECMO support were 0.026 and 0.027 L/h/kg, respectively, very similar to the results of another study (0.0276 L/h/kg), 12 which used a two‐compartment model to describe the PK profile of 24 critically ill patients without ECMO support, suggesting that the impact of ECMO on the polymyxin B PK was likely to be minimal. Compared with another study that included patients with ECMO support, 24 our study showed a higher polymyxin B CL and a lower Vd, and hypoalbuminemia may be the parameter that may explain such PK differences (34.2 ± 3.1 vs. 29.8 ± 1.6).…”
Section: Discussioncontrasting
confidence: 67%
“…23 To the best of our knowledge, only one study had evaluated the PK variability of polymyxin B in patients with ECMO support. 24 Using a non-compartment PK analysis, this study found that ECMO patients had a significantly higher polymyxin B exposure and a significantly lower Vd than non-ECMO patients. These findings are inconsistent with those of other studies conducted in this patient population.…”
Section: What Is Known and Objectivementioning
confidence: 87%
See 3 more Smart Citations